Research on performance evaluation of ecological product value realization under the “Dual Carbon Goals” - Churui Yang; Pengxiang Wang; Rongxin Li; Miaoheng Zhang (Frontiers in Environmental Economics)
IntroductionTo measure the performance level of ecological product value realization, this article selects 16 indicators from four aspects: high-quality development, urban-rural regional coordination, ecological environment governance, and institutional mechanism construction to construct a performance evaluation index system for ecological product value realization mechanism. The entropy weight method is used to calculate the performance level of the whole country and 30 provinces (municipalities) from 2012 to 2022.MethodsThe innovation of this article lies in the first use of the whole country as the research object, constructing a long-term panel data model covering the period of 20122022, and quantitatively analyzing the performance differences and dynamic evolution laws of ecological product value realization in each province through entropy weight method. This national provincial scale research design not only fills the gap in macro level performance evaluation, but also reveals the differences in location characteristics and institutional responses in the transformation of ecological product value in different regions.ResultsThe results show that the performance of the national ecological product value realization mechanism has been increasing year by year, showing explosive growth in 2015, and the growth rate has fluctuated since then.DiscussionIt is suggested to formulate a performance evaluation policy for the realization mechanism of ecological product value based on the goal of building a beautiful China, promote the establishment of ecological product value realization methods and paths with the characteristics of each province (city), conduct performance evaluations on pilot demonstrations and base creation in the national ecological product value realization, and further optimize and improve relevant institutional mechanisms.